2010
DOI: 10.1016/j.jcv.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between HIV-1 viral load quantification in plasma, dried blood spots, and dried plasma spots using the Roche COBAS Taqman assay

Abstract: a b s t r a c tBackground: The use of simplified methods for viral load determination could greatly increase access to treatment monitoring of HIV patients in resource-limited countries. Objective: The aim of the present study was to optimize and evaluate the performance of the Roche COBAS Taqman assay in HIV-RNA quantification from dried blood spots (DBS) and dried plasma spots (DPS). Study design: EDTA blood samples from 108 HIV-infected women were used to prepare 129 DBS and 76 DPS on Whatman 903 card. DBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 15 publications
4
42
3
Order By: Relevance
“…8,10 The results with bDNA reported here are consistent and modestly improved from our previous results using this assay, which indicated that HIV-1 viral load levels were approximately 0.5 log 10 copies/mL lower than those obtained from frozen samples. 8 Although the overall correlation between frozen and dried samples was good (within 0.3 log 10 /mL) and consistent with differences seen with DBS, 11,12 there were some samples around the lower limit of detection that resulted in false negative or positive results. However, all discordant HIV-1 viral load results were no greater than 200 copies/mL.…”
Section: Discussionsupporting
confidence: 59%
“…8,10 The results with bDNA reported here are consistent and modestly improved from our previous results using this assay, which indicated that HIV-1 viral load levels were approximately 0.5 log 10 copies/mL lower than those obtained from frozen samples. 8 Although the overall correlation between frozen and dried samples was good (within 0.3 log 10 /mL) and consistent with differences seen with DBS, 11,12 there were some samples around the lower limit of detection that resulted in false negative or positive results. However, all discordant HIV-1 viral load results were no greater than 200 copies/mL.…”
Section: Discussionsupporting
confidence: 59%
“…The CAP/ CTM also facilitates efficient processing and high throughput of specimens to allow laboratories to rapidly quantify HIV load in large numbers of specimens (21). A high degree of correlation in HIV-1 viral load measurement between plasma and DBS specimens has been reported using the CAP/CTM assay (22). The CAP/CTM has not been widely adopted in Kenya or across sub-Saharan Africa, with the exception of South Africa (23).…”
mentioning
confidence: 99%
“…DBS can be easily collected and stored without being frozen or refrigerated (2,17,22). Several studies have demonstrated the feasibility of DBS as a specimen type for VL testing using different methodologies, although limitations in terms of sensitivity and stability have been noted (3,5,9,10,12,16). In addition, the recognition of distinct subtypes is an important problem in countries where HIV variability is high, and some VL assays occasionally underquantify some variants (19,24).…”
mentioning
confidence: 99%